Efficiency of medical-psychological rehabilitation in patients with acute coronary syndrome - Nesterak, Роксолана; Gasyuk, Мирослава (Psychosomatic Medicine and General Practice, 2019)
Introduction. The problem of rehabilitation of cardiac patients is relevant in modern clinical practice. Cardiovascular disease (CVD) in general and coronary heart disease (CHD) in particular remain in the range of life-threatening diseases, causes of disability and impaired population performance in Ukraine, and work is underway to improve patient's rehabilitation. Purpose. The purpose of the study is to perform a differential analysis of the dynamics of quality of life of patients diagnosed with acute coronary syndrome (ACS) without ST-segment evaluation during the rehabilitation process; to investigate the effectiveness of medical and psychological rehabilitation through the application of the "Program of psychological rehabilitation of cardiac patients by optimizing the internal picture of health". Materials and methods. We examined 135 patients with acute coronary syndrome (ACS) without ST-segment elevation who were assigned conservative or invasive treatment. The study was conducted in the Ivano-Frankivsk Regional Clinical Cardiology Center in the infarct department №2 and rehabilitation. The main diagnostic method of the study was the Seattle Questionnaire and the SF-36, the 36-Item Short-Form Health Survey; additional: conversation, observation; adequate methods of statistical processing of the information received were applied. Results. A comparative analysis of the dynamics of changes in indicators on the scales of the SF-36 questionnaire and an objective medical and psychological study of patients' status, obtained by direct and indirect methods, showed that: Investigation into the dynamics of the quality of life of a cardiac patient at all stages of the rehabilitation process is a valid and reliable way of assessing the quality and effectiveness of cardiac rehabilitation, which allows to determine the integral characteristics of the patient's condition, such as physical, psychological and social components at each key stage of cardiac rehabilitation. The study found that there were objective and subjective causes for the change in the quality of life of patients with acute coronary syndrome (ACS). In particular, it is proved that differences in quality of life indicators of patients in the first stage of rehabilitation depend on the chosen treatment tactics.